The Skeletomuscular System of the Mesosoma of Formica rufa Workers (Hymenoptera: Formicidae). Issue 2 (24th March 2022) - Aibekova, Lazzat; Boudinot, Brendon E; Georg Beutel, Rolf; Richter, Adrian; Keller, Roberto A; Hita-Garcia, Francisco; Economo, Evan P
Abstract: The mesosoma is the power core of the ant, containing critical structural and muscular elements for the movement of the head, legs, and metasoma. It has been hypothesized that adaptation to ground locomotion and the loss of flight led to the substantial rearrangements in the mesosoma in worker ants and that it is likely the ant mesosoma has undergone functional modifications as ants diversified into different ecological and behavioral niches. Despite this importance, studies on the anatomy of the ant mesosoma are still scarce, and there is limited understanding of important variation of internal structures across the ant phylogeny. Recent advances in imaging techniques have made it possible to digitally dissect small insects, to document the anatomy efficiently and in detail, and to visualize these data in 3D. Here we document the mesosomal skeletomuscular system of workers of the red wood ant, Formica rufa Linnaeus, 1761, and use it to establish a 3D atlas of mesosomal anatomy that will serve as reference work for further studies. We discuss and illustrate the configuration of the skeletomuscular components and the function of the muscles in interaction with the skeletal elements. This anatomical evaluation of a 'generalized' ant provides a template for future studies of the mesosoma across the radiation of Formicidae, with the ultimate objective of synthesizing structural, functional, and transformational information to understand the evolution of a crucial body region of ants.